Sub-surface characterisation of tribological contact zone of metal hip prostheses. (September 2015) - Zeng, P; Sharp, J; Rana, A; Thompson, R; Rainforth, W M; Cook, R B
Abstract: Many metal on metal joint failures have been associated with adverse local tissue reactions due to the response of the body to wear debris and corrosion products, released from the bearing surface or the taper interface. Both a carbonaceous layer and an oxide film are reported on the CoCrMo metal joints, which play important roles in the wear resistance of the material. However, there is a lack of quantitative data on the structure and distribution of the carbonaceous layer and the oxide film. The current work provides a detailed investigation of the surface damage on retrieved CoCrMo taper interfaces. In addition, systematic differences in the starting surface structure of biomedical CoCrMo were studied through a comparison of a standard mechanical polished (MP) and an electropolished (EP) surface after reciprocating test. Site-specific FIB/TEM cross-sections show the evidence of the carbonaceous layer and the oxide film on both CoCrMo taper interfaces and MP, EP CoCrMo, ranging from 5 -500 nm depending on the location. The amorphous carbonaceous layer exhibits a π * peak in the EEL spectra, with trace of Ca and N. The oxide film on the taper interfaces has a porous texture and HRTEM indicates chromium oxide nano-crystals in an amorphous background, however, only a very thin oxide film (∼ 2 nm) exists on MP and EP CoCrMo after reciprocating test.